Correlation of Microvessel Density with Tumor Characteristics and Prognostic Factors in Breast Carcinoma - V. VIJAYASREE (I) (Correlation of Microvessel Density with Tumor Characteristics and Prognostic Factors in Breast Carcinoma, 2025)
An abnormal tissue that grows by cellular proliferation more rapidly than normal and continues to grow after the stimuli that instigated the growth cease. Neoplasms show a partial or complete lack of structural organisation & functional coordination with the normal tissue. The term tumor, which literally means swelling, is a synonym of neoplasm. Breast carcinoma arises from the terminal ductal–lobular units of epithelial tissue, which is the mature breast, and represents 10% of the total value.